2021
DOI: 10.1111/jcmm.16650
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐144‐induced KLF2 inhibition and NF‐kappaB/CXCR1 activation promote neutrophil extracellular trap–induced transfusion‐related acute lung injury

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Accumulating evidence has suggested that miR-144-3p expression is deeply tied with immune responses in various diseases. Here, miR-144-3p was found to be upregulated in H37Ra-infected macrophages (RAW264.7 cells and BMDMs), line with earlier findings suggesting the miR-144-3p induction as exposed to BCG or nontuberculous mycobacteria challenge. , Furthermore, compared to healthy people, TB patients had higher miR-144-3p expression in their serum and sputum . These results indicate that miR-144-3p may be crucial in Mtb infection.…”
Section: Discussionsupporting
confidence: 87%
“…Accumulating evidence has suggested that miR-144-3p expression is deeply tied with immune responses in various diseases. Here, miR-144-3p was found to be upregulated in H37Ra-infected macrophages (RAW264.7 cells and BMDMs), line with earlier findings suggesting the miR-144-3p induction as exposed to BCG or nontuberculous mycobacteria challenge. , Furthermore, compared to healthy people, TB patients had higher miR-144-3p expression in their serum and sputum . These results indicate that miR-144-3p may be crucial in Mtb infection.…”
Section: Discussionsupporting
confidence: 87%
“…Pro‐inflammatory neutrophils (Neu1) had downregulated KLF2 . Reduced KLF2 levels can promote neutrophil migration [26] and exacerbate NET‐induced transfusion‐related acute lung injury [27]. In the ISG high neutrophils (Neu2), we observed upregulation of ADGRE5 , also known as CD97 , which may promote migration of ISG high neutrophils to the lungs [28].…”
Section: Resultsmentioning
confidence: 99%
“…TRALI mainly occurs due to the presence of HLA or HNA antibodies in the transfused blood, and in some cases, due to lipids or aging blood cells in the transfused blood (17,18). The "two-hit" theory of TRALI, suggests that the rst hitis triggered by lipopolysaccharide (LPS) endotoxin, which activates receptor endothelial cells and leads to increased expression of intercellular adhesion molecule-1 (ICAM-1) and the release of chemokines that recruit and activate neutrophils (19). The second hit occurs when HLA or HNA antibodies bind to the cognate antigens expressed on the neutrophils, activating a cascade of neutrophil reactions that release reactive oxygen species, leading to damage to surrounding the lung tissue, lung leakage, and the development of TRALI symptoms.…”
Section: Discussionmentioning
confidence: 99%